MEANING, NARROWING OF MEANING, CHANGE OF MEANING IN WORDS MASTERED FROM ARABIC - Z. L. Nasirova (Galaxy International Interdisciplinary Research Journal, 2022)
In the words adopted in the Uzbek language, the narrowness of meaning, the siljish of meaning are analyzed by the example of arabisms.